(untitled) (Research, Society and Development, 2022)
Objective: to analyze the scientific production about the pedagogical and technological resources that favor the online training of nurses, from the perspective of continuing education in health. Method: Integrative Literature Review. The selection and extraction of studies was carried out in January and February 2022, comprising the period from 2016 to 2021. The search occurred in the databases: Virtual Health Library, Scopus and Web of Science. The sample consisted of 10 articles. Results: the studies aimed to describe the stages of development/construction and evaluation/validation of products; analyze interactions in processes of shared knowledge construction. The main resource found was online courses. Clinical cases, videos and tutorials are also among online learning strategies found. Conclusion: Distance Education enables students to adjust their learning to their own time and space, and online courses emerge as an important tool to promote this teaching modality.